Faktor-Faktor yang Mempengaruhi Permintaan Ikan Patin di Desa Palimbangan Sari Kecamatan Haur Gading Kabupaten Hulu Sungai Utara - Yudhi Harianto; Muhammad Solekan (LPPM Sekolah Tinggi Ilmu Pertanian Amuntai, 2019)
The purpose of this study is to identify the factors that influence and measure the level of elasticity of demand for catfish in Palimbangan Sari Village. The study was conducted in Palimbangan Sari Village, Haur Gading District, Hulu Sungai Utara Regency, from July to August 2015. The data used in this study were primary data and secondary data, the sampling technique used was convenience sampling, data analysis used was regression analysis. multiple linear and elasticity analysis. The results showed that the factors that influenced the demand for catfish were the price of catfish, the price of eggs, siamese fish, the number of families, and family income. The price elasticity of catfish is -25,296, meaning that catfish are inelastic, cross elasticity, only the price of eggs and catfish are substitute for catfish because they have a positive elasticity value. From the calculation of income elasticity shows that catfish are normal items